Method for evaluating absorption and precipitation of POE (Polyolefin Elastomer) resin particle aid at high sensitivity
By aging and aging treatment of POE resin particles and additives, combined with characteristic relaxation time testing, the absorption or precipitation of additives is evaluated, and the problem of lack of effective evaluation methods in the prior art is solved, and the POE photovoltaic adhesive film is realized Effective evaluation of performance and guidance on resin particle selection.
Patent Information
- Application Number
- CN202310973193.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art lacks effective methods to evaluate the absorption or precipitation of additives in POE resin particles, resulting in the impact of the performance of POE photovoltaic adhesive film.
By mixing POE resin particles with additives and maturing, then aging under specific conditions, and finally measuring the characteristic relaxation time at 190°C on the characteristic relaxation time tester, the characteristic relaxation time change rate K is calculated to evaluate the Absorption or precipitation of additives.
This method can evaluate the absorption or precipitation of additives in POE resin particles with high sensitivity, and provides an effective reference for the structural selection of POE photovoltaic film formulation additives and resin particles, helping upstream resin manufacturers to optimize their products.
Smart Images

Figure BDA0004376364200000091
Abstract
Description
Technical field:
[0001] The invention relates to a method for highly sensitively evaluating the absorption and precipitation of auxiliary agents of POE resin particles, and belongs to the field of POE photovoltaic packaging material testing. Background technology:
[0002] Photovoltaic film is one of the core materials of photovoltaic modules, mainly including ethylene-vinyl acetate EVA film, ethylene-α-olefin copolymer POE film, etc. Although the cost of the film only accounts for about 4% of the cost of the module, it is a key factor in determining the quality and life of photovoltaic module products. After market testing, the current photovoltaic encapsulation film industry mainly forms a situation where EVA and POE are the mainstream materials. From the composition of the materials, there are mainly EVA transparent film, POE transparent film, EPE three-layer co-extruded film, as well as EVA white film and POE white film. POE is mainly a branched alkane chain without polar groups, so the additives in the single-layer POE film are easily precipitated and migrated to the surface of the film, resulting in a decrease in the friction coefficient of the POE film surface. In addition, the viscoelasticity of the POE material itself is low. If the cell is placed on the film of the production line, if the line speed is too fast, it will cause the cell to slip. In the EPE structure, the additives in the POE layer will migrate to the EVA, which will have a certain impact on the performance of the entire film.
[0003] Characteristic Relaxation Time refers to the time it takes to restore the equilibrium state of stress in the polymer after a constant deformation is applied to the polymer. The characteristic relaxation time is related to the entanglement structure of the polymer chain. If the polymer has long chain branches, as the branched structure increases, the degree of chain entanglement increases, which leads to the extension of the characteristic relaxation time of the polymer. The increase in the degree of entanglement of the polymer chain itself helps to increase the interaction force between the polymer macromolecule chains, thereby enhancing its barrier ability to the migration and precipitation of small molecular substances, reducing the speed at which small molecule additives migrate to the polymer surface, and thus reducing the difficulty of additive precipitation in the POE film. The addition of a small amount of additives, especially cross-linking initiators, will have an important influence on the microstructure of the resin particles, such as the degree of segment entanglement and the strength of the interchain force, under high temperature conditions. Therefore, the changes in the microscopic morphology of the resin particles can be used to characterize the residues of small or trace additives in macroscopic applications.
[0004] If it is possible to judge the absorption or precipitation of the additives in the POE particles in some way, and thus screen out the additives and resin particles that are not prone to precipitation, this provides an effective reference for the formulation of POE photovoltaic films and the screening of resin particles, the raw materials of the films. At present, there is no method on the market to directly evaluate the precipitation performance of additives in POE resin particles and to measure and evaluate the precipitation and absorption capacity of additives of different POE resin particles. Patent CN115343215A first refines and presses the resin particles into films, and then evaluates the absorption of additives by the films. This method starts from the film, so the operation steps are not simple and direct enough, and there is a lack of in-depth thinking on the impact of POE structural characteristics on its additive absorption capacity. Furthermore, this method is difficult for upstream resin manufacturers to select and guide the optimization of POE photovoltaic particle products. In view of this, it is necessary to provide an evaluation method for evaluating the precipitation and absorption performance of POE additives, so as to provide an effective reference for the selection of formulation additives and resin particles in POE photovoltaic films. Summary of the invention
[0005] Technical issues:
[0006] The purpose of the present invention is to provide a highly sensitive method for evaluating the absorption and precipitation of additives of POE resin particles, thereby providing an effective reference for the structural selection of formulation additives and resin particles in POE photovoltaic adhesive films.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] In order to achieve the above object, the present invention provides a method for highly sensitively evaluating the absorption and precipitation of additives of POE resin particles, the method comprising the following steps:
[0009] (a) Sample preparation stage: POE resin particles and additives are mixed and aged, preferably at 35 to 65° C. for 2 to 8 hours to obtain test sample particles;
[0010] (b) Pretreatment: Place the test sample in a ziplock bag, place it for natural aging (preferably, the aging conditions are: 20-35° C., 25% RH-60% RH, 3-10 days) or accelerated aging (preferably, the accelerated aging conditions are: 40-55° C., 25-60% RH, 1-2 days), then take it out to obtain pretreated sample particles;
[0011] (c) Testing stage: The characteristic relaxation time of the test sample and the pretreated sample at 190°C was tested under shear rate conditions ranging from 0.1 rad / s to 500 rad / s to obtain λ0 and λ1; the characteristic relaxation time change rate K was calculated, K = (λ0-λ1) / λ0*100%. The larger the K value, the more serious the precipitation of the additive and the worse the corresponding additive absorption.
[0012] Further, the resin particles in step (a) are ethylene-α-olefin copolymers POE, wherein the α-olefin includes one or more selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene and 1-eicosene.
[0013] Furthermore, the auxiliary agents are peroxide initiators and acrylate crosslinking agents.
[0014] Further, the peroxide initiator is one or more of tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy carbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate, and tert-butyl peroxy-2-ethylhexyl carbonate. The dosage is 0.0001 to 0.01 wt % based on the mass of the POE resin particles.
[0015] Further, the acrylate crosslinking agent is one or more of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate. The dosage is 0.0001-0.01wt% based on the mass of POE resin particles.
[0016] The positive effects of the present invention are: ① Based on the differences in POE chain structures, the present invention is helpful for upstream resin manufacturers to conduct structure-activity relationship research, and has guiding significance for upstream manufacturers to upgrade and iterate resin products under the requirements of photovoltaic applications; ② The sample preparation process of the method is simple, and the particle-film preparation process is omitted, so that the method has the characteristics of rapid response; ③ The method is based on the microstructure of resin particles, the amount of additives used is small, the detection sensitivity is high, and it has the ability to detect trace residues and trace additions of additives. DETAILED DESCRIPTION
[0017] The present invention is further described below by specific examples, which are only used as explanations of the present invention and do not limit the scope of the present invention. In this application, "parts" and "%" are by weight unless otherwise specified.
[0018] Main materials:
[0019] Ethylene-octene copolymer A: 8660, manufacturer: Dow;
[0020] Ethylene-octene copolymer B: 8669, manufacturer: Dow;
[0021] Ethylene-butene copolymer C: LF575, manufacturer: LG;
[0022] Ethylene-butene copolymer D: LF675, manufacturer: LG;
[0023] Tert-butyl peroxy-2-ethylhexyl carbonate, Aladdin, purity 95%;
[0024] Tert-butyl peroxyisopropyl carbonate, Aladdin, purity 95%;
[0025] Trimethylolpropane triacrylate, Aladdin, purity 95%;
[0026] Pentaerythritol triacrylate, Aladdin, purity 95%;
[0027] Test instruments and methods:
[0028] Characteristic relaxation time tester: TA Co. ARES-G2 rheometer. The complex viscosity was obtained from the angular velocity of the copolymer at 190°C, angular velocity of 0.1 rad / s to 500 rad / s and 5% strain, and the characteristic relaxation time was calculated by fitting using the following Carreau-Yasuda equation.
[0029] η(γ)=η ∞ +(η0-η ∞ )[1+(λγ) α ] (n-1) / α
[0030] η(γ): Viscosity
[0031] η ∞ : Infinite viscosity
[0032] η0: Zero shear viscosity
[0033] λ: relaxation time
[0034] γ: shear rate
[0035] α: Material constant
[0036] n: shear thinning index
[0037] Example 1
[0038] Sample preparation: Ethylene-octene copolymer A was fully mixed with 0.0001% by weight of tert-butyl peroxy-2-ethylhexyl carbonate and 0.0001% by weight of trimethylolpropane triacrylate, and then aged in an oven at 35° C. for 8 h to obtain a test sample. The relaxation time λ0 of the test sample resin particles at 190° C. was measured on a characteristic relaxation time tester;
[0039] Pretreatment: Place the test sample in a ziplock bag and put it into a constant temperature and humidity room at 20°C and 25% RH. Take it out after 3 days to obtain a pretreated sample. Take the pretreated sample resin particles and measure the relaxation time λ1 at 190°C on a characteristic relaxation time tester; calculate the characteristic relaxation time change rate K, K = (λ0-λ1) / λ0*100%, the corresponding data are shown in Table 1.
[0040] Example 2
[0041] Sample preparation: Ethylene-octene copolymer B, 0.0005% by weight of tert-butyl peroxy-2-ethylhexyl carbonate and 0.0005% by weight of trimethylolpropane triacrylate were fully mixed, and then aged in an oven at 45° C. for 6 hours to obtain a test sample. The relaxation time λ0 of the test sample resin particles at 190° C. was measured on a characteristic relaxation time tester;
[0042] Pretreatment: Place the test sample in a ziplock bag and put it into a constant temperature and humidity room at 30°C and 45% RH. Take it out after 7 days to obtain a pretreated sample. Take the pretreated sample resin particles and measure the relaxation time λ1 at 190°C on a characteristic relaxation time tester; calculate the characteristic relaxation time change rate K, K = (λ0-λ1) / λ0*100%, the corresponding data are shown in Table 1.
[0043] Example 3
[0044] Sample preparation: Ethylene-butene copolymer C, 0.0008% by weight of tert-butyl peroxy-2-ethylhexyl carbonate and 0.0008% by weight of trimethylolpropane triacrylate were fully mixed, and then aged in an oven at 65° C. for 2 h to obtain a test sample. The relaxation time λ0 of the test sample resin particles at 190° C. was measured on a characteristic relaxation time tester;
[0045] Pretreatment: Place the test sample in a ziplock bag and put it into a constant temperature and humidity room at 35°C and 60% RH. Take it out after 10 days to obtain a pretreated sample. Take the pretreated sample resin particles and measure the relaxation time λ1 at 190°C on a characteristic relaxation time tester; calculate the characteristic relaxation time change rate K, K = (λ0-λ1) / λ0*100%, the corresponding data are shown in Table 1.
[0046] Example 4
[0047] Sample preparation: Ethylene-butene copolymer D was fully mixed with 0.001% by weight of tert-butyl peroxyisopropyl carbonate and 0.001% by weight of pentaerythritol triacrylate, and then aged in an oven at 55° C. for 6 h to obtain a test sample. The relaxation time λ0 of the test sample resin particles at 190° C. was measured on a characteristic relaxation time tester;
[0048] Pretreatment: Place the test sample in a ziplock bag and put it into a constant temperature and humidity room at 40°C and 25% RH. Take it out after 1 day to obtain a pretreated sample. Take the pretreated sample resin particles and measure the relaxation time λ1 at 190°C on a characteristic relaxation time tester; calculate the characteristic relaxation time change rate K, K = (λ0-λ1) / λ0*100%, the corresponding data are shown in Table 1.
[0049] Example 5
[0050] Sample preparation: Ethylene-butene copolymer D was fully mixed with 0.005% by weight of tert-butyl peroxyisopropyl carbonate and 0.005% by weight of pentaerythritol triacrylate, and then aged in an oven at 55° C. for 4 h to obtain a test sample. The relaxation time λ0 of the test sample resin particles at 190° C. was measured on a characteristic relaxation time tester;
[0051] Pretreatment: Place the test sample in a ziplock bag and put it into a constant temperature and humidity room at 45°C and 45% RH. Take it out after 1 day to obtain a pretreated sample. Take the pretreated sample resin particles and measure the relaxation time λ1 at 190°C on a characteristic relaxation time tester; calculate the characteristic relaxation time change rate K, K = (λ0-λ1) / λ0*100%, the corresponding data are shown in Table 1.
[0052] Example 6
[0053] Sample preparation: Ethylene-butene copolymer D was fully mixed with 0.01% by weight of tert-butyl peroxyisopropyl carbonate and 0.01% by weight of pentaerythritol triacrylate, and then aged in an oven at 35°C for 6 hours to obtain a test sample. The relaxation time λ0 of the test sample resin particles at 190°C was measured on a characteristic relaxation time tester;
[0054] Pretreatment: Place the test sample in a ziplock bag and put it into a constant temperature and humidity room at 55°C and 60% RH. Take it out after 2 days to obtain a pretreated sample. Take the pretreated sample resin particles and measure the relaxation time λ1 at 190°C on a characteristic relaxation time tester; calculate the characteristic relaxation time change rate K, K = (λ0-λ1) / λ0*100%, the corresponding data are shown in Table 1.
[0055] Comparative Example
[0056] According to the method of Example 1 of patent CN115343215A, ethylene-octene copolymer A and 0.005% by weight of tert-butyl peroxy-2-ethylhexyl carbonate are mixed and refined, pressed into a 0.4 mm thick sheet on a flat vulcanizer, cut into 20*10 cm strips to obtain a test sample, and the test sample is placed on the embossed surface, and the initial friction coefficient F0 is measured on a friction coefficient meter; pretreatment: the test sample is placed in a ziplock bag, put into a -5°C refrigerator, taken out after 1 day, and restored at room temperature for 3h to obtain a pretreated sample, and the pretreated sample is placed on the embossed surface, and the friction coefficient F1 is measured on the friction coefficient meter; the friction coefficient change rate (R) is calculated to obtain the friction coefficient change rate (R): R=(F0-F1)·100% / F0, R=0.02%.
[0057]
[0058] From the comparison of the performance test data of the embodiments described in the above table, it can be seen that:
[0059] It can be seen from the examples that the characteristic relaxation time change rate K between different additives and different particles can be compared horizontally through the method described in the patent of the present invention. The larger the K value, the more serious the additive precipitation, which corresponds to the worse the additive absorption. Therefore, for upstream resin manufacturers, the development of POE particles with a low characteristic relaxation time change rate will help improve the additive absorption of the film in actual use by downstream film manufacturers. In addition, in the comparative example of this patent, when the method of patent CN115343215A is used to add 0.005% by mass of additives to conduct an additive precipitation evaluation experiment, the original patent method fails. Therefore, when trace amounts of additives are added, the evaluation method provided by the present invention has the characteristics of high detection sensitivity and low additive content response.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A highly sensitive method for evaluating the absorption and precipitation of additives in POE resin particles, characterized in that: The method comprises the following steps: (a) Sample preparation stage: POE resin particles are mixed with additives and then aged to obtain test sample particles; (b) Pretreatment: placing the test sample in a ziplock bag and subjecting it to natural aging or accelerated aging for a period of time, then taking it out to obtain pretreated sample particles; (c) Testing stage: The characteristic relaxation time of the test sample and the pretreated sample at 190°C was tested under shear rate conditions ranging from 0.1 rad / s to 500 rad / s to obtain λ0 and λ1; the characteristic relaxation time change rate K was calculated, K = (λ0-λ1) / λ0*100%. The larger the K value, the more serious the precipitation of the additive and the worse the corresponding additive absorption.
2. The method according to claim 1, characterized in that: The POE resin particles in the step (a) are ethylene-α-olefin copolymers POE, wherein the α-olefin includes one or more selected from propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene and 1-eicosene.
3. The method according to claim 1 or 2, characterized in that The auxiliary agents are peroxide initiators and acrylate crosslinking agents.
4. The method according to any one of claims 1 to 3, characterized in that : In the step (a), the dosage of the two additives is 0.0001 to 0.01 wt % based on the mass of the POE resin particles.
5. The method according to any one of claims 1 to 4, characterized in that: In the step (a), the mixture is aged in an oven at 35 to 65° C. for 2 to 8 hours.
6. The method according to any one of claims 1 to 5, characterized in that: The natural aging conditions are 20-35° C., 25% RH-60% RH, and 3-10 days; and / or the accelerated aging conditions are 40-55° C., 25% RH-60% RH, and 1-2 days.
7. The method according to any one of claims 3 to 5, characterized in that The peroxide initiator is one or more of tert-butyl peroxy isopropyl carbonate, 2,5-dimethyl-2,5-(bis-tert-butylperoxy)hexane, tert-butyl peroxy carbonate-2-ethylhexyl ester, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-butyl peroxy 2-ethylhexyl carbonate, tert-amyl peroxy carbonate, tert-butyl peroxy 3,3,5-trimethylhexanoate, and tert-butyl peroxy-2-ethylhexyl carbonate.
8. The method according to any one of claims 3 to 7, characterized in that: The acrylate crosslinking agent is one or more of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate, tricyclohexane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate.
Citation Information
Patent Citations
Method for evaluating precipitation performance of different assistants in POE (Polyolefin Elastomer) adhesive film
CN115343215A